2014
DOI: 10.1177/0022219414528539
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Written Expression in Children With Reading Comprehension Difficulties

Abstract: Several studies have highlighted that children with reading comprehension difficulties also have problems in tasks that involve telling a story, in writing or verbally. The main differences identified regard poor comprehenders' lower level of coherence in their productions by comparison with good comprehenders. Only one study has compared poor and good comprehenders' performance in both modalities (oral and written), however, to see whether these modalities differently influence poor comprehenders' performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 45 publications
1
42
1
Order By: Relevance
“…This was surprising considering that previous research has found significant reciprocal connections between reading comprehension and text composition (Abbott, Berninger & Fayol, 2010). Some previous studies also indicate that students with poor reading comprehension may find writing challenging (Carretti, Motta & Re, 2016;Cragg & Nation, 2006). The lack of significant correlations between reading comprehension and writing in this study may be due to the construction of the reading comprehension task in Grade 3.…”
Section: Discussioncontrasting
confidence: 83%
“…This was surprising considering that previous research has found significant reciprocal connections between reading comprehension and text composition (Abbott, Berninger & Fayol, 2010). Some previous studies also indicate that students with poor reading comprehension may find writing challenging (Carretti, Motta & Re, 2016;Cragg & Nation, 2006). The lack of significant correlations between reading comprehension and writing in this study may be due to the construction of the reading comprehension task in Grade 3.…”
Section: Discussioncontrasting
confidence: 83%
“…Certainly, any disorder could co-occur with a WD, and efforts to address other relationships have been studied in children exhibiting ADHD symptoms (Re, Pedron, & Cornoldi, 2007), reading comprehension deficits (Carretti, Motta, & Re, 2014; Carretti, Re, & Arfè, 2011), and developmental dyslexia (Berninger, Nielsen, Abbott, Wijsman, & Raskind, 2008); however, data from the present study provide some of the first rates of WD + RD co-occurrence in a young elementary school population. Conversely, it is important to note that although there appears to be an overlap of WDs and RDs, there were equal percentages of students who experienced a WD-Only across each of the four grades.…”
Section: Discussionmentioning
confidence: 88%
“…A discrepancy between reading comprehension and word-level decoding with additional requirements that decoding skills are within the normal range and that comprehension scores fall below a given percentile or cut point (Cain & Towse, 2008; Carretti, Motta, & Re, 2014; Catts et al, 2006; Henderson, Snowling, & Clarke, 2013; Kasperski & Katzir, 2012; Megherbi, Seigneuric, & Ehrlich, 2006; Nation, Clarke, Marshall, & Durand, 2004; Nation, Snowling & Clark, 2007; Nesi, Levorato, Roch & Cacciari, 2006; Pelegrina, Capodieci, Carretti, & Cornoldi, 2014; Pimperton & Nation, 2014; Ricketts, Nation, & Bishop, 2007; Shankweiler et al, 1999; Tong et al, 2011; Tong et al, 2014).…”
Section: Identifying Children With Scdmentioning
confidence: 99%
“…The view that comprehension problems are general to oral language and reading is supported by multiple investigations. Children with SCD have demonstrated weaknesses related to a variety of oral language domains, such as semantic processing, listening comprehension, and syntactic ability (Carretti, Motta, & Re, 2014; Nation & Snowling, 2000; see Cain & Oakhill, 2011 and Justice, Mashburn, & Petscher, 2013 for longitudinal evidence). When compared to typical readers, these children also tend to perform significantly poorer on measures tapping verbal working memory skills (see Carretti, Borella, Cornoldi, & De Beni, 2009).…”
Section: Theoretical and Empirical Support For Alternative Hypothesesmentioning
confidence: 99%